2016
DOI: 10.3389/fpls.2016.01136
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Photosystem II: The Mechanisms for Avoidance and Tolerance of Light and Heat Stresses are Closely Linked to Membrane Fluidity of the Thylakoids

Abstract: When oxygenic photosynthetic organisms are exposed to excessive light and/or heat, Photosystem II is damaged and electron transport is blocked. In these events, reactive oxygen species, endogenous radicals and lipid peroxidation products generated by photochemical reaction and/or heat cause the damage. Regarding light stress, plants first dissipate excessive light energy captured by light-harvesting chlorophyll protein complexes as heat to avoid the hazards, but once light stress is unavoidable, they tolerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 113 publications
(166 reference statements)
1
96
1
1
Order By: Relevance
“…Several studies suggest that thylakoids require a particularly high level of fluidity regulation for the proper functioning of the embedded proteins, which occupy about 70% of the membranes (Kirchhoff et al ., ; Dormann and Holzl, ; Yamamoto, ). As these membranes provide the matrix for the photosynthetic machinery, the fluidity regulation processes we highlight in this study are likely essential mechanisms for survival and competitiveness of a cyanobacterial strain at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that thylakoids require a particularly high level of fluidity regulation for the proper functioning of the embedded proteins, which occupy about 70% of the membranes (Kirchhoff et al ., ; Dormann and Holzl, ; Yamamoto, ). As these membranes provide the matrix for the photosynthetic machinery, the fluidity regulation processes we highlight in this study are likely essential mechanisms for survival and competitiveness of a cyanobacterial strain at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…PCC 6803 and Synechococcus sp. PCC 7942, a number of mutant studies have demonstrated that PG is physiologically essential and is notably involved in the activity of both photosystems, influencing the dimerization and reactivation of core complexes (Sakurai et al, 2003;Bogos et al, 2010;Yamamoto, 2016). X-ray crystallographic analysis of photosystem II at 1.9 Å resolution has identified 5 PG molecules bound to photosystem II, directly connected to the D1 protein and plastoquinone Q B (Itoh et al, 2012;Mizusawa and Wada, 2012).…”
Section: Cold-induced Desaturations Of Acyl Chains In Synechococcus Smentioning
confidence: 99%
“…The structure of the thylakoid membranes is dependent on lipids located either at the membrane‐exposed surface of protein complexes or at well‐defined positions of the proteins (Yamamoto, ). Heat stress‐induced inactivation of photosystem II is likely to be affected by the alterations in the fluidity of the thylakoid membranes (Yamamoto, ). Based on the results presented in this study, our findings support a major role of HSP21 in stabilizing the thylakoid membranes by directly interacting with the core subunits of PSII, although we cannot rule out the possibility that HSP21 may function in protecting the fluidity of the thylakoid membranes under heat stress.…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that chemical and biological reactions occurring in the thylakoids can be regulated by membrane fluidity (Mizusawa and Wada, ; Yamamoto, ). The structure of the thylakoid membranes is dependent on lipids located either at the membrane‐exposed surface of protein complexes or at well‐defined positions of the proteins (Yamamoto, ). Heat stress‐induced inactivation of photosystem II is likely to be affected by the alterations in the fluidity of the thylakoid membranes (Yamamoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…Combination of high light and moderate heat stress negatively affects PSII, with additive or synergistic effects on thylakoid membrane fluidity, lipid peroxidation, and oxidative damage (Quiles, 2006;Yamamoto, 2016). Moreover, chloroplast signaling is involved in heat stress responses (Dickinson et al, 2017).…”
Section: Integrative Effects Of Stress Hubs and Cell Surveillance Smentioning
confidence: 99%